Hubungan Tingkat Kecemasan Hospitalisasi Dengan Sleep Disturbance Pada Anak Usia Prasekolah Di Rumah Sakit Tk. Iii Dr. Reksodiwiryo Padang Tahun 2025 - Oresti, Syalvia; Oktizulvia, Conny; Putri, Fitrah Yulita Dwi (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Sleep is one of the basic human needs, so the need for sleep is a need for all ages. The need for sleep for children is a component that plays a role in their physical and intellectual growth. This study aims to determine the relationship between hospitalization anxiety levels and sleep disturbance in preschool children at TK. III Dr. Reksodiwiryo Hospital, Padang. The purpose of this study is to find out the relationship between hospitalization anxiety levels and sleep disturbance in preschool children at TK. III Dr. Reksodiwiryo Hospital, Padang, 2025.This research method uses a cross-sectional approach with an accidental sampling technique. This study was conducted in February - August 2025, research and data collection were conducted on April 17, 2025 to May 19, 2025. The population at the Dr. Reksodiwiryo Padang Kindergarten III Hospital was 329 people and the sample size was 77 people.More than half of the respondents (72.7%) experienced sleep disturbance. More than half of the respondents (51.9%) experienced mild anxiety. There is a relationship between anxiety levels and sleep disturbance in preschool children at the Dr. Reksodiwiryo Padang Kindergarten III Hospital (p-value 0.001 <0.05).It is hoped that the leadership of Dr. Reksodiwiryo Padang Level III Hospital can provide a more child-friendly hospital environment, for example, animated images can be provided in each children's ward to reduce children's anxiety and fear. Taking into account the facts of hospitalization, patient demographics, and children's general anxiety levels, children with more colorful hospital rooms experience lower anxiety compared to those with ordinary wards. This study provides evidence that hospital design reduces the psychological impact of hospitalization. Although what is experienced as a supportive design will vary based on the child's developmental stage.